If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2y + -1 = X Reorder the terms: -1 + 4y + 2y = X Combine like terms: 4y + 2y = 6y -1 + 6y = X Solving -1 + 6y = X Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 6y = 1 + X Combine like terms: -1 + 1 = 0 0 + 6y = 1 + X 6y = 1 + X Divide each side by '6'. y = 0.1666666667 + 0.1666666667X Simplifying y = 0.1666666667 + 0.1666666667X
| 6(2y+3)= | | 2a+a+10+44=18 | | 16t^2-29T+6=0 | | 7x-18y=15 | | -52-2x=60+5x | | (2x-6)(4x+2)=(8x+3)(x-4) | | 4x+2y-1=z | | 2x+3x=27 | | 2x^2+32=8x | | -8c+9=1 | | -3x-14=-5x+34 | | 15d-19=14+4d | | 1.25x=1500 | | 8p-27=13+3p | | -x-7=4 | | 84=2g+r | | 3.2=0.6x | | 9e-9=7+e | | 8=y+17 | | -37+4x=17+7x | | 6h-17=3+h | | 7=3+5a | | .05x+x=681 | | 11-5=9z+7 | | 5+4n=28 | | 2x+3+4x=x+8 | | 4s-1=5+s | | 3g-4=6+g | | y=62.5+15x | | 6(x-1)=2x-5 | | 5(5-3)+2m=27 | | 3x+12(x-2)=13 |